LITERASI SEKOLAH SEBAGAI PENINGKATAN KUALITAS PENDIDIKAN - ASNGADI ROFIQ (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
ABSTRACT This study aims to find out that the growing level of school literacy can improve the quality of education. Library research method using a qualitative approach. It can be concluded that school literacy is very urgent for the world of education. The development of the world of science and technology is so fast in this era of globalization, for that it must be immediately balanced by mastering the science and technology, by learning (reading). Because by not immediately compensating automatically will soon be left behind. Seeing the weaknesses that exist for the Indonesian people, both the ability to read, the love of reading, the lack of reading materials for our students so that they lose or are left behind from other nations, it is only natural that efforts must be made to catch up. There are various efforts, including the promotion of the school literacy movement (SLS). As the Minister of Education and Culture Regulation No.23 of 2015 concerning School Literacy. In the implementation of the school literacy movement that went well by paying attention to the objectives, principles, stages, involving various parties, utilizing infrastructure, maximizing the literacy team, it turned out that it had an impact on improving the quality of education in general and the success of students in particular.